Practical approach to transfusion management of post‐partum haemorrhage. Issue 1 (5th January 2021) - Frigo, Maria Grazia; Agostini, Vanessa; Brizzi, Agostino; Ragusa, Antonio; Svelato, Alessandro
Abstract: Objectives: To describe transfusion management during post‐partum haemorrhage (PPH) and the usefulness of standard or point‐of‐care (POC) laboratory tests for guiding haemostatic management. Background: PPH is the leading cause of maternal mortality and severe maternal morbidity worldwide. Despite the efforts made in recent years, PPH is often burdened by preventable death. Recent data from the active Italian Obstetric Surveillance System (ItOSS) highlighted the following main critical issues: inadequate communication between healthcare professionals, inability to correctly and promptly assess the severity of haemorrhage, delays in diagnosis and treatment, failure to request blood promptly and inappropriate monitoring post‐partum. Materials and Methods: Data in the literature have been compared with the rotational thromboelastometry (ROTEM)‐ and the thromboelastography (TEG)‐guided algorithms applied in the authors' departments. Results: PPH transfusion therapy may have an empirical approach based on the standard use of blood products or a targeted approach based on coagulation monitoring by laboratory or POC tests. Here, the authors describe how they manage PPH in their departments, according to the Italian guidelines, along with the addition of a ROTEM‐ and a TEG‐guided algorithms developed by themselves. Conclusion: Although the proposed algorithms have not been validated by trials or observational studies conducted in our departments, we believe that these indications could be useful for supporting clinical practice. Furthermore, we deem it appropriate to emphasise the importance of a multidisciplinary approach and the need for standardised and shared protocols to support the decisions of healthcare professionals.